Somatic instability of the expanded GAA repeats in Friedreich's ataxia. - Ashlee Long; Jill S Napierala; Urszula Polak; Lauren Hauser; Arnulf H Koeppen; David R Lynch; Marek Napierala (PLoS ONE, 2017)
Friedreich's ataxia (FRDA) is a genetic neurodegenerative disorder caused by transcriptional silencing of the frataxin gene (FXN) due to expansions of GAA repeats in intron 1. FRDA manifests with multiple symptoms, which may include ataxia, cardiomyopathy and diabetes mellitus. Expanded GAA tracts are genetically unstable, exhibiting both expansions and contractions. GAA length correlates with severity of FRDA symptoms and inversely with age of onset. Thus, tissue-specific somatic instability of long GAA repeats may be implicated in the development of symptoms and disease progression. Herein, we determined the extent of somatic instability of the GAA repeats in heart, cerebral cortex, spinal cord, cerebellar cortex, and pancreatic tissues from 15 FRDA patients. Results demonstrate differences in the lengths of the expanded GAAs among different tissues, with significantly longer GAA tracts detected in heart and pancreas than in other tissues. The expansion bias detected in heart and pancreas may contribute to disease onset and progression, making the mechanism of somatic instability an important target for therapy. Additionally, we detected significant differences in GAA tract lengths between lymphocytes and fibroblast pairs derived from 16 FRDA patients, with longer GAA tracts present in the lymphocytes. This result urges caution in direct comparisons of data obtained in these frequently used FRDA models. Furthermore, we conducted a longitudinal analysis of the GAA repeat length in lymphocytes collected over a span of 7-9 years and demonstrated progressive expansions of the GAAs with maximum gain of approximately 9 repeats per year. Continuous GAA expansions throughout the patient's lifespan, as observed in FRDA lymphocytes, should be considered in clinical trial designs and data interpretation.